Impact of salinity on CO2containment security in highly heterogeneous reservoirs - Al-Khdheeawi, E.; Vialle, Stephanie; Barifcani, Ahmed; Sarmadivaleh, Mohammad; Zhang, Y.; Iglauer, Stefan (Wiley, 2017)
© 2017 Society of Chemical Industry and John Wiley & Sons, Ltd. It is well established that brine salinity can vary substantially in prospective CO 2 geo-storage reservoirs. However, the impact of salinity on containment security has received only little attention. We thus used a compositional reservoir simulation to evaluate the effect of salinity on CO 2 plume migration and CO 2 trapping capacities in a 3D heterogeneous reservoir. The used heterogeneous reservoir consists of two formations: the bottom part of the reservoir is a fluvial reservoir, and the top part represents a near-shore environment. Our results clearly indicate that salinity has a significant influence on CO 2 migration and the relative amount of mobile, residual, and dissolved CO 2 . Lower salinity decreases CO 2 mobility and migration distance, and enhances residual and solubility trapping significantly. We thus conclude that brine salinity is an important impact factor in the context of CO 2 geo-storage, and that less saline reservoirs are preferable CO 2 sinks due to increased storage capacity and containment security.